Arbaʿīn al-ʿAlāʾī fi kalām al-ʿalī - Āybayk, Yūsuf b., (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of Islamic literature, the 'Forty Traditions' genre goes back as far as the 3th/9th century at least and exists in all of Islam's major and minor languages. It finds its origin in the tradition saying that whoever commits forty traditions to memory will be reckoned among the jurists on Resurrection Day. Collections vary, from a simple listing of the basic teachings of Islam to more dedicated works around some specific theme, in either case with or without a commentary. There are also collections of sayings of the Prophet's son-in-law ʿAlī b. Abī Ṭālib (d. 40/661), from among which al-Sharīf al-Raḍī's (d. 406/1088) Nahj al-Balāgha is the most famous. The work by Yūsuf b. Āybayk published here is a Persian text in the arbaʿūn tradition but based on the Nahj al-balāgha . Dedicated to the Qaramānid ruler of Anatolia ʿAlāʾ al-Dīn Beg (d. 800/1397-8), it deals mostly with ethics explained from a mystical perspective.